Cortisol as a Blood Biomarker for Monitoring Endurance Training - A Narrative Review - Stadnik, Luiza; Kozłowska, Alicja; Przybysz, Karolina; Woroniecka, Natalia; Dzwonkowska, Adela; Zienkiewicz, Natalia; Trocka, Daria; Rachoń, Jarosław; Szerenos, Nicol; Dzwonkowski, Jakub (Quality in Sport, 2026)
Background. Blood cortisol is a key biomarker of hypothalamic-pituitary-adrenal (HPA) axis activity and is widely used in sports science to assess physiological and psychological stress. However, its interpretation is limited by considerable biological variability and multiple influencing factors. Aim. To summarize current evidence on the physiological role of blood cortisol in endurance exercise and its usefulness for monitoring training load, recovery, and adaptation. Material and methods. A narrative review of peer-reviewed studies, systematic reviews, meta-analyses, and guidelines on cortisol physiology, exercise endocrinology, and athlete monitoring was conducted. Results. Blood cortisol reflects the physiological stress response and supports metabolic and immune regulation during endurance exercise. Acute increases are a normal adaptive response, whereas persistent alterations may indicate excessive training stress when interpreted in context. Due to circadian variation and other confounding factors, single measurements have limited value. Current evidence favors longitudinal within-athlete monitoring combined with physiological, psychometric, hormonal, and performance measures. Conclusions. Blood cortisol is a useful component of endurance athlete monitoring but should not be used as a stand-alone marker. Its greatest value lies in repeated standardized assessments interpreted within a multimodal monitoring approach. Key words: cortisol, endurance training, exercise physiology, training monitoring, training load, physiological stress, overtraining syndrome, athlete monitoring, Hypothalamic-Pituitary-Adrenal Axis